Design and construct an uninterruptible power supply system - Wee, Wei Ze. (2011)
This report aims to present a transportable and environmentally friendly form of the uninterruptible power supply (UPS) system. The author summarizes existing UPS technologies and delves into the energy storage methods that are crucial to a power system. The report takes a novel approach into the development of a design that eases off the dependence on existing main supply systems.